Saúde e segurança do trabalho nas práticas arquivísticas no Amazonas - Carvalho, Lauriane Reis (Brasil, 2022)
The present work aims to present an analysis of the application of health and safety in archival practices in Amazonas. A survey was carried out through a questionnaire made available to graduates of the Archivology course at the Federal University of Amazonas, with regard to the knowledge and awareness of archivists professionals regarding the use of personal protective equipment and the prevention of physical risk agents, chemical, biological, ergonomic and mechanical in the work environment. Concepts of Work Safety are discussed, presenting some regulatory norms, as well as the idealization and archival observations on preservation and conservation actions aimed at health practices, and later the analysis of the questionnaire. In this way, from the information collected, we seek to promote a reflection on the practices of Work Safety applied in the archives of Amazonas, showing how the two interact and complement each other in agreement and harmony.